1996
DOI: 10.3358/shokueishi.37.104
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Tea Extracts on Cariogenic Bacterium (Streptococcus mutans)

Abstract: Antimicrobial activities of tea extracts on the cariogenic bacterium, Streptococcus mutans, were studied. Extracts of green and black tea leaves effectively suppressed the growth of S. mutans as compared with those of oolong and Pu-erh tea leaves. Ethyl acetate and n-butanol extracts of both green and black tea leaves and the non-dialyzable fraction of the water-soluble fraction of black tea leaves showed strong antimicrobial activities on S. mutans. Catechins were found in the ethyl acetate and n-butanol extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 0 publications
0
14
0
4
Order By: Relevance
“…[9,[13][14][15][16] Briefly, S. mutans was grown overnight in YN with glucose. After 16 hours 0.1 mL of the stationary phase culture from the broth was transferred to a culture tube that contained 15 mL of the broth.…”
Section: Determination Of Antimicrobial Activity (Plate Dilution Assay)mentioning
confidence: 99%
“…[9,[13][14][15][16] Briefly, S. mutans was grown overnight in YN with glucose. After 16 hours 0.1 mL of the stationary phase culture from the broth was transferred to a culture tube that contained 15 mL of the broth.…”
Section: Determination Of Antimicrobial Activity (Plate Dilution Assay)mentioning
confidence: 99%
“…There have been reports that BTND exhibited an anti-tumor-promoting effect in mouse epidermal JB6 cell lines, an inhibitory effect on duodenal carcinogenesis in mice (15,17), induction of apoptotic cell death in cancer cells (18), and an antibacterial action (14). Moreover, it has been considered that the active ingredients of BTND are polyphenolic compounds of flavonols and gallates, quinic acid and carbohydrates of D-glucose and Dgalactose units (15).…”
Section: Discussionmentioning
confidence: 99%
“…For example, tea aqueous non-dialysate (TND) is the generic name of the fraction of water-soluble polymer components with molecular weights over 12000 extracted from tea leaves. It has already been reported that black tea aqueous non-dialysate (BTND), which is well characterized among several kinds of TND, exhibits anti-microbial activity against a cariogenic bacterium (14). Therefore, the activity of BTND against H. pylori was investigated in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, polyphenols present in green tea contain high levels of catechins and theaflavins and have very strong antibacterial properties. 50 Some other studies have evaluated the anticariogenic properties of green tea by assessing its direct effect on microorganisms. 51 In vitro studies have shown that catechins present in green tea prevent adhesion of Streptococci to tooth surfaces.…”
Section: Discussionmentioning
confidence: 99%